Shari’ah governance for Islamic banking: evidence from diverse regulatory environments - Haron, Razali; Nomran, Naji (IGI Global, 2020)
Due to the rapid global growth in Islamic banking and finance industry, supervisory authorities in many countries have developed different Shari’ah governance (SG) regulatory systems to regulate this industry. However, the current SG practices across jurisdictions still suffer from some drawbacks. This chapter highlights some issues related to the differences across jurisdictions in adopting various SG regulatory practices and supports the discussion using descriptive analysis. The findings indicate that Islamic banks (IBs) demonstrate higher levels of financial performance, on average, when located in regulated jurisdictions, in jurisdictions that restrict cross-membership of scholars in Shari’ah Supervisory Boards (SSBs), and in jurisdictions adopting Centralized supervision model (CSGM). The findings also show that IBs in jurisdictions adopting Reactive regulatory model report the worst performance in comparison with the other models (Passive, Pro-active, Interventionist and Minimalist).